KEBEBASAN BERPENDAPAT DAN BEREKSPRESI DI MEDIA SOSIAL PRESPEKTIF HUKUM DAN HAK ASASI MANUSIA - -, Khairani Hasibuan; Aspani, Budi; Fitriah, Fitriah (Faculty of Law, University of Palembang, 2024)
The characteristic of a country that has progressed in the era of globalization is by seeing how the role of the internet or social media can change the mindset and behavior of its people. The role of the internet today has a fairly important role because almost all activities or information can be accessed on the internet. The internet provides many interesting features and can be a place for people to express themselves, either by providing education, suggestions and criticism, although in fact what is written and said on social media can cause pros and cons. However, as a country that adheres to a democratic system, the government as a facilitator must give its citizens the right to freely express and express their opinions, either directly or through social media. Freedom of opinion and expression is a basic right that has been guaranteed by the constitution in various countries, including Indonesia. Where this right has been universally recognized and guaranteed in various legal instruments, both nationally and internationally. However, freedom of opinion and expression often clashes with other interests such as national security, public order, and the rights of others. This is a challenge to control so that limitations and regulations are given to this freedom, especially in the context of the spread of hoax information, hate speech and violation of privacy. The purpose of this study is to examine and analyze freedom of opinion and expression on social media from a legal perspective, both in terms of relevant national and international regulations.